2021
DOI: 10.1016/j.jlr.2021.100135
|View full text |Cite
|
Sign up to set email alerts
|

Altered HDL proteome predicts incident CVD in chronic kidney disease patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…We tested the hypothesis that the levels of one or more HDL proteins associate with incident CVD in subjects with T1DM. HDL was isolated from freshly thawed serum by ultracentrifugation, and its protein composition was quantified by isotope-dilution MS/MS with PRM ( 26 , 27 ). An unadjusted analysis revealed that 11 proteins were differentially expressed in HDL isolated from the control group and from the incident CVD group ( supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We tested the hypothesis that the levels of one or more HDL proteins associate with incident CVD in subjects with T1DM. HDL was isolated from freshly thawed serum by ultracentrifugation, and its protein composition was quantified by isotope-dilution MS/MS with PRM ( 26 , 27 ). An unadjusted analysis revealed that 11 proteins were differentially expressed in HDL isolated from the control group and from the incident CVD group ( supplemental Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We used targeted proteomics with isotope-dilution parallel reaction monitoring (PRM) to quantify HDL proteins ( 26 , 27 ). Briefly, LC-ESI-MS/MS analyses were performed in the positive-ion mode with an ultrahigh-resolution accurate mass Orbitrap Fusion Lumos Tribrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA) coupled to a nanoACQUITY UPLC (Waters, Milford, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Untersteller et al showed that neither the quantity of HDL-C nor the composition or function of HDL-C could predict cardiovascular outcome among CKD patients independently ( 25 ). Shao et al found that the protein cargo of HDL-C could be used as a biomarker and mediator for elevated CVD risk in CKD patients ( 26 ). Calabresi et al reported that acquired plasma lecithin cholesterol acyltransferase (LCAT) deficiency was a major cause of low plasma HDL levels in patients with CKD, making it an attractive therapeutic target to reverse dyslipidaemia and reduce potential cardiovascular events ( 27 ).…”
Section: Discussionmentioning
confidence: 99%